The relationship of the application of dıfferent learnıng technıques and teachıng models wıth the school success of students - Antonijević, Radovan; Radenović, Dragana (Norma, 2022)
The subject of this research is the connection between the the application of different learning techniques and teaching models and the school performance of students in the field of mathematics and Serbian language. The aim of the research is to identify the basic characteristics of the connection between contextual factors of school environment regarding the application of different learning techniques and teaching models and school success of students in the field of mathematics and Serbian language. Six hundred seventh grade students participated in the research. A descriptive method was used, and data were collected using a scaling technique. The results show that the greater application of different teaching models and techniques of learning in the class, the higher is the grade in mathematics and Serbian language. The emphasis is on effective management of the learning process by the teacher.